2D Monolayer MoS2–Carbon Interoverlapped Superstructure: Engineering Ideal Atomic Interface for Lithium Ion Storage. (18th May 2015) - Jiang, Hao; Ren, Dayong; Wang, Haifeng; Hu, Yanjie; Guo, Shaojun; Yuan, Haiyang; Hu, Peijun; Zhang, Ling; Li, Chunzhong
<x xml:space="preserve">Abstract</x> A novel strategy for the controlled synthesis of 2D MoS2/C hybrid nanosheets consisting of the alternative layer‐by‐layer interoverlapped single‐layer MoS2 and mesoporous carbon (m‐C) is demonstrated. Such special hybrid nanosheets with a maximized MoS2/m‐C interface contact show very good performance for lithium‐ion batteries in terms of high reversible capacity, excellent rate capability, and outstanding cycling stability.